2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the variation in sensory test results using Semmes-Weinstein monofilaments

Abstract: The purpose of this study is to examine the variability in sensory test of tactile results using Semmes-Weinstein monofilament (SWM). At present, several methods for measuring the tactile sensitivity are clinically used in diabetic peripheral neuropathy screening. One of these methods is a touch test that uses a device with nylon SWMs, i.e., SWMs embedded in a plastic handle. A small pushing force is applied at the handle to bow the filaments. Because of its ease and simplicity, the SWM test is conducted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…In the manual operation experiment (experiment 1), we measured the buckling force and compared the force values among 10 trials. The human hand motion with a monofilament differed among individuals, as in the previous study [21]. On average, although the buckling force monotonically decreased in 10 successive trials, the velocity of the hand motion and the contact angle did not show monotonic changes.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In the manual operation experiment (experiment 1), we measured the buckling force and compared the force values among 10 trials. The human hand motion with a monofilament differed among individuals, as in the previous study [21]. On average, although the buckling force monotonically decreased in 10 successive trials, the velocity of the hand motion and the contact angle did not show monotonic changes.…”
Section: Discussionsupporting
confidence: 51%
“…However, several studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ] have previously reported concerns about the mechanical properties of monofilaments (for a review, see [ 16 ]). For example, Booth et al [ 17 ] reported that the maximum recovery of the buckling force in any monofilament is achieved within 24 h and discussed the variability of force on a simulated skin surface in the results of the SWMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A monofilament test was performed to evaluate foot sense in specific areas. 11 All patients were examined at the beginning and post management at the eighth week and sixth month. VAS and FFI scores were completed by phone at the sixth month.…”
Section: Data Collectionmentioning
confidence: 99%
“…Os dispositivos analógicos, mesmo os validados, usualmente manifestam poder de reprodutividade com maiores desvios que seus paralelos digitais 6,7 , como é o caso do estesiômetro do tipo monofilamentos de Semmes-Weinstein 8 . Em parte, o comprometimento da acurácia dos dados durante a coleta é causado por variabilidade entre avaliadores diferentes ou pela dispersão entre as áreas das secções transversais de um monofilamento para outro, com valores nominais notadamente diferentes 9 . Isso pode ser um problema quando o monofilamento em teste tem secção transversal maior que o necessário para estimular o campo receptivo da pele ou o atual estado de sensibilidade.…”
Section: Introductionunclassified